New paradigms of understanding a child, quality of childhood and childhood institutionalization - Jurčević-Lozančić, Anka (Array, 2019)
According to the contemporary understanding, a child is an integral being, an active participant in his/her own education, a curious and competent being with diverse interests, capabilities, knowledge and understanding, and a person who, driven by an innate curiosity, explores the world surrounding him/her, and actively acquires knowledge. These new paradigms have influenced the revision of understanding a child and his/her childhood, which is not only a preparatory stage for the future, but the period of life that has its own values and culture. Childhood is a process that is contextualized, always in relation to a specific space, time and culture, and varies according to different conditions and cultures in which it occurs. And it is the status of a child, conceived by adults, that is reflected in the overall education of the child, thus becoming a decisive factor in determining his/her social and ethical identity. This paper discusses the basic attitudes relating to a child and his/her childhood, upbringing, development and education within family and institutional surroundings.